2003
DOI: 10.1603/0013-8746(2003)096[0679:ioahbh]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Africanized Honey Bee (Hymenoptera: Apidae) Mitochondrial DNA: Validation of a Rapid Polymerase Chain Reaction-Based Assay

Abstract: Polymerase chain reaction (PCR)-ampliÞed mitochondrial DNA (mtDNA) assays have been used in studies of the Africanization process in neotropical feral and managed honey bee populations. The approach has been adopted, in conjunction with morphometric analysis, to identify Africanized bees for regulatory purposes in the United States such as in California. In this study, 211 Old World colonies, representing all known introduced subspecies in the United States, and 451 colonies from non-Africanized areas of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…Similar disagreement between mitochondrial and nuclear markers occurs in Africanized honey bees (Lobo 1995) and in A. m. iberica (Cánovas 2008(Cánovas , 2011. In studies of subspecies identification, it was recommended to use mtDNA only for initial screening (Rortais et al 2011) or together with morphometrics or nuclear markers (Nielsen et al 1999;Pinto et al 2003). It is sometimes suggested that molecular methods are better than morphological ones (Page 1998); however, not all of them are suitable for discrimination of all honey bee subspecies (Sheppard et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Similar disagreement between mitochondrial and nuclear markers occurs in Africanized honey bees (Lobo 1995) and in A. m. iberica (Cánovas 2008(Cánovas , 2011. In studies of subspecies identification, it was recommended to use mtDNA only for initial screening (Rortais et al 2011) or together with morphometrics or nuclear markers (Nielsen et al 1999;Pinto et al 2003). It is sometimes suggested that molecular methods are better than morphological ones (Page 1998); however, not all of them are suitable for discrimination of all honey bee subspecies (Sheppard et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…m. scutellata) cytochrome b PCR-amplified fragment (Crozier et al 1991;Pinto et al 2003) were not analyzed further. The Egyptian A. m. lamarckii is not discriminated from eastern and western European honeybees using the cytochrome b/BglII assay (Pinto et al 2003). Colonies that exhibited a non-A.…”
Section: Mitochondrial Dna Analysismentioning
confidence: 99%
“…Studies of the invasive Africanized honeybee (Apis mellifera L.) in the United States hold promise for addressing some of these issues because (1) the pre-Africanized managed and feral honeybee populations have been genetically characterized (Schiff et al 1994;Sheppard 1995, 1996;Pinto et al 2003), (2) Africanized honeybees have recently invaded the United States (Rubink et al 1996) and formation of a hybrid zone is ongoing, and (3) the arrival of the Africanized honeybee was nearly coincidental with arrival of one of the most destructive pests of honeybees, the parasitic mite Varroa destructor (De Guzman et al 1997).…”
mentioning
confidence: 99%
“…(Rubink et al, 1996;Sugden and Williams, 1990). European and African (Apis mellifera scutellata) maternal lineage was confirmed using mitochondrial DNA (mtDNA) analysis (Pinto et al, 2003). Africanized honey bee nuclear DNA is introgressed with an unknown amount of European nuclear DNA and mtDNA type represents an unbroken maternal lineage (Pinto et al, 2005).…”
Section: Worker Ovarian Follicle Development Responses To Africanizedmentioning
confidence: 94%